Stability of the pension system of the Republic of Belarus in the context of demographic tendencies - Belov, Andrei A. (Journal of the Belarusian State University. Sociology, 2019)
Projection of size and sex-age structure of the population of the Republic of Belarus until 2050 is made in the article on the base of component method. Two projection scenarios are considered. Based on the projection data, the expected increase in the number and proportion of persons aged 60 years and over, as well as the number of retirement age persons and the old-age-dependency ratio are analyzed. It is concluded that the three-year increase of retirement age in 2017–2022 leads to a decrease in the pension burden. However, the trend towards aging of the population completely negates the effect of this reform by 2025. New reforms will be needed to save the pension burden at the same level in 2023–2050. The possible increase in the retirement age by 2050 is assessed.
Keywords: demographic projection; pension system; old-age-dependency ratio; population aging; population size; expectation of life at birth